THE IMPACT OF SCHOOL ENVIRONMENTAL FACTORS TO THE MOTOR DEVELOPMENT OF STUDENTS WITH AUTISM SPECTRUM DISORDER (ASD) IN PINAGLABANAN ELEMENTARY SCHOOL, SAN JUAN CITY (Proceedings of International Conference on Special Education, 2017)
Environment has a big impact to every child’s development. It can affect their social, emotional or physical development. Thus, this study aims to determine the impact of the school environmental factors to the motor development of students with Autism Spectrum Disorder (ASD). The study is both descriptive and qualitative in nature. It restricted its respondents only to the administrator, SpEd teachers and parents/guardians of the students. And it has been limited to the use of self administered survey questionnaire and interview questionnaire. A cross sectional study design was utilized to determine the impact of the school environmental factors to the motor development of students with autism spectrum disorder (ASD) ages 5 to 12 years old that were under the school year 2013-2014 in Pinaglabanan Elementary School San Juan City, Philippines.Based on the summary of the impact of environmental factors on the motor development of students with autism assessed by the school administrators and SPED teachers it resulted with the average impact (X = 2.3) and likewise, the parents strongly agreed the same level of impact was also on the average, (X =2.66), respectively. Given that, in Special Education the environmental factors should not be taken for granted. This should be included in the school’s main priorities for improvement. The school administrator should review and check the different school environmental factors and its importance. The evaluation of the school environmental factors should be strengthened. Concrete evaluation of the motor skills of the students should then be done and properly documented.